Circular RNA VRK1 facilitates pre‐eclampsia progression via sponging miR‐221‐3P to regulate PTEN/Akt. Issue 6 (18th March 2021) - Li, Ziwei; Zhou, Xinyi; Gao, Wenyan; Sun, Manni; Chen, Haiying; Meng, Tao
Abstract: Pre‐eclampsia (PE) is a worldwide pregnancy‐related disorder. It is mainly characterized by defect migration and invasion of trophoblast cells. Recently, circular RNAs (circRNAs) have been believed to play a vital role in PE. The expression patterns and the biological functions of circRNAs in PE remain elusive. Here, we performed a circRNA microarray to identify putative PE‐related circRNAs. Bioinformatics analyses were used to screen the circRNAs which have potential relationships with pre‐eclampsia, and we identified a novel circRNA (circVRK1) that was up‐regulated in PE placenta tissues. By using HTR‐8/SVneo cells, circVRK1 knockdown significantly enhanced cell migration and invasion abilities, as well as epithelial‐mesenchymal transition (EMT). Mechanistically, we found that circVRK1 and PTEN could function as the ceRNAs to miR‐221‐3p. Overexpression of miR‐221‐3p promoted cell migration, invasion and EMT via regulating PTEN. The cotransfection of miR‐221‐3p inhibitor or PTEN reversed the effect from circVRK1 knockdown. Moreover, the circVRK1/miR‐221‐3p/PTEN axis greatly regulated Akt phosphorylation. In general, circVRK1 suppresses trophoblast cell migration, invasion and EMT, by acting as a ceRNA to miR‐221‐3p to regulate PTEN, and further inhibit PI3K/Akt activation. The purpose of this paper is to open wide insights to investigate the onset of PE and provide new potential therapeutic targets in PE.